Human Trafficking on Illegal, Unreported and Unregulated Fishing Cases as Transnational Crime on Indonesia Coastal Boundary - Sartika Saimima, Ika Dewi; Clara Ignatia Tobing; Mochammad Syafruddin Rezky Sanaky (Dinasti Research, 2022)
Indonesian strategic archipelago allows rapid migration of goods and services to its neighbor countries. Along with goods and services, the wide coastal area also facilitates migrant worker to enter and exit Indonesia through several ports. First and foremost interference on the borderless coastal boundary is Illegal, Unreported and Unregulated (IUU) Fishing. The IUU foreign fishing vessels frequently transporting illegal migrant worker obtained through human trafficking, people smuggling, forced labor, child exploitation, torture, and discrimination. This practices can then be categorized as one of the transnational organized crime at sea. This paper focuses on the studies of notorious cases of human trafficking on IUU Fishing. This journal will also observe the lack of prevention measure of transnational crime on UNCLOS and utilization of bilateral and multilateral treaties on IUU Fishing.